microRNA–mRNA Networks Linked to Inflammation and Immune System Regulation in Inflammatory Bowel Disease - Síbia, Carina de F. de [UNESP]; Quaglio, Ana E. V. [UNESP]; Oliveira, Ellen C. S. de [UNESP]; Pereira, Jéssica N. [UNESP]; Ariede, Jovita R. [UNESP]; Lapa, Rainer M. L.; Severino, Fábio E. [UNESP]; Reis, Patricia P. [UNESP]; Sassaki, Lígia Y. [UNESP]; Saad-Hossne, Rogerio [UNESP] (MDPI, 2024)
The molecular processes linked to the development and progression of Crohn’s disease (CD) and ulcerative colitis (UC) are not completely understood. MicroRNAs (miRNAs) regulate gene expression and are indicated as diagnostic, prognostic, and predictive biomarkers in chronic degenerative diseases. Our objectives included the identification of global miRNA expression in CD and UC, as well as miRNA target genes, miRNA–mRNA interaction networks, and biological functions associated with these different forms of inflammatory bowel disease (IBD). Methods: By performing a comprehensive meta-analysis, we integrated miRNA expression data from nine studies in IBD. We obtained detailed information on significantly deregulated miRNAs (fold change, FC ≥ 2 and p < 0.05), sample type and number, and platform applied for analysis in the training and validation sets. Further bioinformatic analyses were performed to identify miRNA target genes, by using the microRNA Data Integration Portal tool. We also sought to identify statistically enriched pathways of genes regulated by miRNAs using ToppGene Suite. Additional analyses were performed to filter for genes expressed in intestinal tissue using the European Bioinformatics Institute (EBI) database. Results: Our findings showed the upregulation of 15 miRNAs in CD and 33 in UC. Conversely, six miRNAs were downregulated in CD, while seven were downregulated in UC. These results indicate a greater deregulation of miRNAs in UC compared to CD. Of note, miRNA target genes were enriched for immune system regulation pathways. Among significantly deregulated miRNAs with a higher number of miRNA–target gene interactions, we identified miR-199a-5p and miR-362-3p altered in CD, while among UC case patients, miRNA–target gene interactions were higher for miR-155-5p. Conclusions: The identified miRNAs play roles in regulating genes associated with immune system regulation and inflammation in IBD. Such miRNAs and their target genes have the potential to serve as clinically relevant biomarkers. These findings hold promise for enhancing the accuracy of diagnoses and facilitating the development of personalized treatment strategies for individuals with various forms of IBD.
Keywords: Crohn’s disease; inflammatory bowel disease; meta-analysis; microRNA; ulcerative colitis